Complex coacervates based on recombinant mussel adhesive proteins: their characterization and applications. Issue 42 (16th October 2017) - Kim, Hyo Jeong; Yang, Byeongseon; Park, Tae Yoon; Lim, Seonghye; Cha, Hyung Joon
Abstract : Recombinant mussel adhesive protein-based complex coacervates are an effective underwater adhesive and have significant potential in practical applications that require underwater adhesion. Abstract : Complex coacervates are a dense liquid phase of oppositely charged polyions formed by the associative separation of a mixture of polyions. Coacervates have been widely employed in many fields including the pharmaceutical, cosmetic, and food industries due to their intriguing interfacial and bulk material properties. More recently, attempts to develop an effective underwater adhesive have been made using complex coacervates that are based on recombinant mussel adhesive proteins (MAPs) due to the water immiscibility of complex coacervates and the adhesiveness of MAPs. MAP-based complex coacervates contribute to our understanding of the physical nature of complex coacervates and they provide a promising alternative to conventional invasive surgical repairs. Here, this review provides an overview of recombinant MAP-based complex coacervations, with an emphasis on their characterization and the uses of such materials for applications in the fields of biomedicine and tissue engineering.